Microscopic Characterization of Au Nanoparticles Prepared by Sputtering Method - Michalcová, Alena; Vojtěch, Dalibor (Manufacturing Technology Journal, 2016)
This article offers a novel method of gold nanoparticles preparation which increases their obsevation feasibility. Gold nanoparticles were prepared by sputtering of 6 nm of gold on surface of NaCl crystals and consequent annealing. Gold nanoparticles were separated from the substrate mechanically in the ultrasonic bath. The preparation of gold nanoparticles on NaCl substate is extremely versatile. It enables to descibe size and shape of the individual nanoparticles much better than usually used SEM and AFM techniques, it enables to see the lattice arrangements and also to do more precise chemical analysis without the influence of the substrate. It is applicable for characterization of temperature-, time-, chemical composition- and atmosphere influence on morphology of gold nanoparticles. The nanoparticles were observed by HRTEM. In our case, the influence of carbon addition on morphology of gold nanoparticles was studied by sputtering one or two carbon interlayes in the gold layer. It was found out that one carbon interlayer slightly descrease nanoparticle size. On the other hand, two carbon interlayers lead to formation of irregular large shapes of the gold particles.
Keywords: TEM; nanoparticles; sputtering